A phase 2 study of E6011, an anti-Fractalkine monoclonal antibody, in patients with rheumatoid arthritis inadequately responding to biological disease-modifying antirheumatic drugs. Issue 4 (4th July 2021) - Tanaka, Yoshiya; Takeuchi, Tsutomu; Yamanaka, Hisashi; Nanki, Toshihiro; Umehara, Hisanori; Yasuda, Nobuyuki; Tago, Fumitoshi; Kitahara, Yasumi; Kawakubo, Makoto; Torii, Kentaro; Hojo, Seiichiro; Kawano, Tetsu; et al.
Abstract: Objectives: To evaluate the safety and efficacy of E6011, a novel humanized anti-fractalkine monoclonal antibody, in patients with active rheumatoid arthritis (RA) with an inadequate response to biological disease-modifying antirheumatic drugs (DMARDs). Methods: Active RA patients inadequately responding to biological DMARDs were randomly assigned to placebo or E6011 400-mg group at a 1:1 ratio, and administered E6011 at weeks 0, 1, 2, and subsequently every 2 weeks. Primary endpoint was American College of Rheumatology (ACR)20 response at week 12. Results: Of 64, 33 received placebo, 31 received E6011 400-mg. The ACR20 response rate at week 12 (non-responder imputation) was 27.3% and 22.6% in the placebo and E6011 groups, respectively. ACR50, ACR70 response rates at week 12 were 3.0%, 0% in the placebo and 9.7%, 3.2% in the E6011 group. Exploratory PK exposure analysis revealed that the effect of E6011 tended to be clearer in patients with higher serum trough E6011 concentration. E6011 was well tolerated with no notable safety concerns. Conclusions: E6011 400-mg was well tolerated but had no clear efficacy at week 12 in RA patients with inadequate response to biologics. Further investigations are warranted to determine the optimal clinical dose and evaluation period for E6011.